(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article studies the impact of the shell-and-tube heat exchanger used in the oil refining industry, which is a hot topic today, on the hydrodynamic regimes of the diffuser-confuser profile pipe on the heat exchange process.